Employee Turnover In Organizations: A Systematic Literature Review (SLR) Of Determinants Across Industries And Countries - Firial Dhia Salsabila; Nur Wening (PT. Anagata Sembagi Education, 2025)
Employee turnover affects organizational stability and increases human resource costs such as recruitment and training. This article presents a systematic literature review (SLR) to map the most frequently reported determinants of employee turnover/turnover intention across organizational contexts. A thematic synthesis yields eight clusters: (1) compensation and rewards, (2) job dissatisfaction, (3) career development, (4) training and competence development, (5) work environment, (6) job pressure and work stress, (7) organizational culture, and (8) recognition. These findings can inform retention strategy prioritization and future research agendas.